Exploring financial accountability issues among NPO in Malaysia as part of money laundering preventive measure / Norli Ali...[et al] - Ali, Norli (Research Management Institute (RMI), 2011)
This study examines the current state of financial reporting disclosure practices by 60 non-profit organisations that have registered under the Companies Commission of Malaysia. Subsequently, this study examined the factors influencing the non-profit organisations on their level of financial reporting disclosure practices. The results show that all non-profit organisations that submitted their annual reports prepared the statement of Income and Expenditure, Balance Sheet and Cash Flow Statement although the level of financial reporting disclosure differs. The results also show that total revenues and total assets influencing the level disclosure. Non-profits organization with high total assets and total revenue tends to disclosed more details items in the Income and Expenditure and balance sheet account. Review of Asia Pacific Group reports on non-profit organization suggest that Malaysian regulatory bodies should undertake domestic reviews of their non-profit organisation sector. This study provides further understanding on the transparency and accountability practices among non-profit organisations in Malaysia.